Galatheid and chirostylid crustaceans (Decapoda: Anomura) from a cold seep environment in the northeastern South China Sea - Dong, Dong; Li, Xinzheng (Zootaxa, 2015)
Six species of squat lobsters from a cold seep field in the northeastern South China Sea are studied. Two new species, Uroptychus jiaolongae n. sp. and U. spinulosus n. sp., are described, and their distinctions from the related species are detailed. Two species, Munidopsis tuberosa Osawa, Lin & Chan, 2008 and M. verrilli Benedict, 1902, are herein reported for the first time from a cold seep/hydrothermal vent environment. The number of squat lobsters species associated with those chemosynthetic environments now stands at forty-one.